Current research on motivational factors of teachers as knowledge workers / Nur Afifah Yakub, Nur Farhana Zaidi and Ahmad Nadzri Mohamad. - Yakub, Nur Afifah; Zaidi, Nur Farhana; Mohamad, Ahmad Nadzri (Universiti Teknologi MARA Cawangan Selangor, 2018)
The motivational factors of knowledge workers and teachers has been the major interest in research world for many years. However, very few current research on motivational factors of teachers as knowledge workers. The purpose of this paper is to review the literature on intrinsic and extrinsic motivational factors of teachers as knowledge workers, focused on professional development, job autonomy, job security, reward and recognition, monetary incentives and working environment. This review is significant to educational policymaker, school administrator and the government to have an insight into motivational factors of teachers as knowledge workers and how these factors can increase teacher job satisfaction.